A Video- and Case-Based Curriculum on the Management of Alcohol Use Disorder for Internal Medicine Residents - Sara A. Spinella; Diana Samberg; Melissa McNeil; Scott D. Rothenberger; Payel Jhoom Roy; Andrea E. Carter (Association of American Medical Colleges, 2022)
Introduction Alcohol use disorder (AUD) is commonly undertreated. Physicians cite discomfort with AUD medication as a barrier to treatment. While several curricula teach and assess screening and brief interventions, few teach and assess learner knowledge of treatment options. Methods We created a video- and case-based curriculum for internal medicine residents delivered by 16 internal medicine faculty in three 30-minute sessions at four clinic sites. Learner knowledge, attitudes, and confidence were assessed before and after the curriculum. We used qualitative methods to evaluate learner reflections. We also assessed faculty satisfaction with the curriculum. Results Of 153 residents receiving the curriculum, 35 (23%) completed both pre- and postsurveys. Median percent correct on knowledge questions improved from 67% pre- to 80% postcurriculum (p < .001). Confidence increased for all three items assessing it, with a notable increase in confidence with pharmacotherapy (2.9 pre- vs. 4.5 postcurriculum on a 7-point Likert scale with high scores indicating greater confidence, p < .001). Positive attitudes toward people with AUD increased from 3.4 pre- to 3.9 postcurriculum (p < .001) on a 7-point Likert scale. Learners continued to express concerns about prescribing logistics, the role of primary care, and management of ongoing use. Thirteen of 16 faculty (83%) completed the postcurricular survey; all said they would be happy to facilitate again. Discussion Implementation of this curriculum for the management of AUD improved resident knowledge, attitudes, and confidence in AUD treatment. The curriculum was acceptable to faculty and is ideal for programs looking to expand teaching about AUD.